Analisis Kemampuan Representasi Matematis dalam Menyelesaikan Masalah Kontekstual materi PLSV Melalui Pendekatan PMRI - Ikhfina Khoirun Nisa; Agnia Rahmata Putri; Siti Nina Ainun Bidara Rohmah; Dewi Hamidah (Indonesian Mathematics Education Journal, 2024)
This study examines the mathematical representation ability of seventh grade junior high school students in solving contextual problems of Linear Equation One Variable (PLSV) through Indonesian Realistic Mathematics Education (PMRI). Using qualitative methods and randomly selected samples, this study evaluates how students apply mathematical representations in the context of PLSV through essay assessments, documentation, and interviews. Data analysis was conducted according to the Miles and Huberman method, which includes data reduction, data presentation, and conclusion drawing. Results showed that PMRI was effective in improving students' mathematical representation ability, enabling them to effectively translate and solve everyday problems into mathematical models. The findings confirm the importance of PMRI as a learning approach that facilitates conceptual understanding and practical application of mathematics, suggesting wider application of PMRI in mathematics learning to develop strong mathematical representation skills among students.